Green manure/cover crops for improved livestock feeding: IPSR Innovation Profile - Thierfelder, Christian L. (CGIAR System Organization, 2022)
Green manure/cover crops (GMCC) are plants that are grown in cropping systems not primarily for their grain but to provide groundcover, feed, and to fertilize the soil. In most cases green manures are legumes that fix nitrogen from the air and, once killed by rolling, spraying, or uprooting, provide large amounts of biomass. GMCCs may be grown either as rotational crops or as intercrops with the main crop. When they are introduced as intercrops, they are commonly killed before introducing the next main crop. Cover crops may be annual or perennial and in the case of being perennial, they may be maintained into the next season without replanting. Cover crops may be either leguminous or non-leguminous crops. Leguminous cover crops are mostly preferred by resource-constrained farmers due to their residual nitrogen effect. GMCCs have different growth habits and hence give different benefits depending on their characteristics. They also may serve different purposes in the farming systems depending on their local context.